2016
DOI: 10.3389/fncel.2016.00226
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mRNA Translation by MID1: A Common Mechanism of Expanded CAG Repeat RNAs

Abstract: Expansion of CAG repeats, which code for the disease-causing polyglutamine protein, is a common feature in polyglutamine diseases. RNA-mediated mechanisms that contribute to neuropathology in polyglutamine diseases are important. RNA-toxicity describes a phenomenon by which the mutant CAG repeat RNA recruits RNA-binding proteins, thereby leading to aberrant function. For example the MID1 protein binds to mutant huntingtin (HTT) RNA, which is linked to Huntington's disease (HD), at its CAG repeat region and ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…Interestingly, the MID1 complex appears to bind to expanded CAG repeats with higher affinity than to non-expanded repeats. In agreement with a role for MID1 and mTORC1 in promoting canonical translation of these transcripts, translation is increased upon inhibition of PP2Ac, and decreased upon knockdown of MID1 or inhibition of mTORC1 (Griesche et al, 2016; Krauss et al, 2013). Whether this mechanism also contributes to RAN translation is unknown.…”
Section: Non-canonical Translation Of Nucleotide Repeat Expansionssupporting
confidence: 67%
“…Interestingly, the MID1 complex appears to bind to expanded CAG repeats with higher affinity than to non-expanded repeats. In agreement with a role for MID1 and mTORC1 in promoting canonical translation of these transcripts, translation is increased upon inhibition of PP2Ac, and decreased upon knockdown of MID1 or inhibition of mTORC1 (Griesche et al, 2016; Krauss et al, 2013). Whether this mechanism also contributes to RAN translation is unknown.…”
Section: Non-canonical Translation Of Nucleotide Repeat Expansionssupporting
confidence: 67%
“…We have recently shown that mRNAs carrying CAG repeats bind to a protein complex containing the ubiquitin ligase midline 1 (MID1) in a repeat size-dependent manner. Through ubiquitination MID1 regulates PP2A (protein phosphatase 2A) and mTOR (mechanistic target of rapamycin) activities and the translation of associated mRNAs ( Krauss et al, 2013 ; Griesche et al, 2016 ). Disruption of the MID1/PP2A/mTOR protein complex leads to an increase of PP2A activity, a decrease of mTOR activity and a reduction of translation rates of mRNAs with expanded CAG repeats ( Krauss et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are also additional regulatory connections between the polyglutamine disorders that affect protein translation. For example, the MID1-translation regulatory protein complex binds and regulates the translation of CAG expansions in the canonical ATG-initiated frame in a length dependent manner in HD and several SCAs [26]. It will be interesting to determine if this regulatory mechanism also influences RAN translation.…”
Section: An Expanding Field: Updates On Ran-associated Disordersmentioning
confidence: 99%